(untitled) (World Bulletin of Public Health, 2022)
The developing immune system, along with the endocrine and nervous systems, is most sensitive to the effects of various environmental pollutants. Immunotoxicity of pesticides is a global problem, and our republic is no exception in this regard. In recent years, extensive research has been conducted around the world to identify the mechanisms of adverse effects of various types of pesticides on the immune system of humans and animals, to develop methods for early diagnosis of IV and their prevention. It should be noted that most of these studies were conducted in adults or mature animals. Uncovering the laws of growth and formation of the immune system of offspring in such conditions is of great scientific and practical interest.